Cyclical Effects of the Composition of Government Purchases - Aziz, Jahangir (IMF Working Papers; Working Paper ;, 1997)
This paper constructs a general equilibrium model with monopolistically competitive firms and endogenous markups where government spending consists of both consumption and investment goods. It is shown that when markups are countercyclical, increases in the share of investment goods in aggregate government expenditure entail a trade-off between greater long- run efficiency and higher short-run volatility. Estimates based on the model, calibrated to the postwar U.S. economy, show that the effects on output, employment, and welfare can be significant.